Tango & Cash - Konchalovsky, Andrei; Brion, James; Jack Palance; James Hong; Kurt Russell; Marc Alaimo; Teri Hatcher; Sylvester Stallone (USA Guber-Peters Company, 1989)
Ray Tango and Gabriel Cash are narcotics detectives who, while both being extremely successful, can't stand each other. Crime Lord Yves Perret, furious at the loss of income that Tango and Cash have caused him, frames the two for murder. Caught with the murder weapon on the scene of the crime, the two have alibi. Thrown into prison with most of the criminals they helped convict, it appears that they are going to have to trust each other if they are to clear their names and catch the evil Perret.
Two cops are framed and must clear their names.
Randy Feldman
Language(s): English
Subtitle(s): English, Turkish
Keywords: Comedy; Crime; Thriller; Action